Imlikasi Hukum Terhadap Putusan Pkpu Analisi Putusan Nomor 188 K/Pdt.Sus-Pkpu/2013 - Ruliza Wardatul ’Uzma (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law Number 37 of 2004 Concerning Bankruptcy and Suspension of Debt Payment Obligations, PKPU is an effort to reach an Agreement or Mutual Agreement between the debtor and creditor which is carried out with the intention of submitting a peace plan in the form of an offer of payment of either part or all of the debt that has matured to the creditor regarding the settlement of debts. Furthermore, in the results of the analysis of Decision PKPU Number 188 K/Pdt.Sus-PKPU/2013, the Debtor has violated the provisions of Article 222 paragraph (2) of the Law, it is explained that for debtors who have more than one creditor and the debtor does not pay at least one debt that has matured and can be collected, he is declared bankrupt by a court decision, either at the request of the debtor himself or at the request of one or more of his creditors, Legal Implications of Decision No. 08/PKPU/2012/PN.Niaga.Mks Debtor PT.Kopi Jaya Comrpora as the debtor, seeing from the trial facts, the author agrees with the decision of the panel of judges.